The legacies of the Basin of Mexico - Cordova, Carlos E., 1965-; Morehart, Christopher T. (University Press of Colorado, 2023)
"This volume celebrates the contributions from The Basin of Mexico: The Ecological Processes in the Evolution of a Civilization by William T. Sanders, Jeffrey R. Parsons, and Robert S. Santley. This influential work synthesized the results of the Basin of Mexico survey projects, while providing lines of research in Mesoamerica"--